The Anonymous and Unusual Seder ʿAvodah ‮ʾaḥaleh lerṿokhev shaׁmayim‬‎ - Bekkum, Wouter J. van (Zutot, 2026)
In this contribution we offer an edited text with commentary and a full English translation of one Seder ʿAvodah in the Adler Collection of the Jewish Theological Seminary, ENA 2385, fol. 26-27. What is very striking about this piyyut is the way in which the poet has abridged the obligatory subjects of the ʿAvodah. There are surprising omissions in the description of the creation of the world, but there are also activities of the High Priest that receive extra emphasis. All in all, this is a Seder ʿAvodah that needs to be studied within the framework of this venerable and longstanding genre within medieval Hebrew hymnology.